A Chlorophyte Alga Utilizes Alternative Electron Transport for Primary Photoprotection . Issue 4 (26th May 2020) - Ware, Maxwell A.; Hunstiger, Darcy; Cantrell, Michael; Peers, Graham
Abstract : Constitutive small antennae, alternative electron transport, and an efficient PSII turnover capacity enable Desmodesmus armatus to photosynthesize efficiently. Abstract: The green alga Desmodesmus armatus is an emerging biofuel platform that produces high amounts of lipids and biomass in mass culture. We observed D. armatus in light-limiting, excess-light, and sinusoidal-light environments to investigate its photoacclimation behaviors and the mechanisms by which it dissipates excess energy. Chlorophyll a / b ratios and the functional absorption cross section of PSII suggested a constitutively small light-harvesting antenna size relative to other green algae. In situ and ex situ measurements of photo-physiology revealed that nonphotochemical quenching is not a significant contributor to photoprotection; however, cells do not suffer substantial photoinhibition despite its near absence. We performed membrane inlet mass spectrometry analysis to show that D. armatus has a very high capacity for alternative electron transport (AET) measured as light-dependent oxygen consumption. Up to 90% of electrons generated at PSII can be dissipated by AET in a water–water cycle during growth in rapidly fluctuating light environments, like those found in industrial-scale photobioreactors. This work highlights the diversity of photoprotective mechanisms present in algal systems, indicating that nonphotochemical quenching is not necessarily required for effective photoprotection in some algae, and suggests that engineering AET may be an attractive target for increasing the biomass productivity of some strains.